Rectal cancer with severe distal spreading - A. A. Nevolskikh; T. P. Berezovskaya; N. A. Gorban; L. M. Kondrashova; L. N. Titova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
The aim of clinical case presentation. To show features of distal tumor spread at patients with local progression of rectal cancer by original case presentation.Features of clinical case. At the patient of young age with rectal adenocarcinoma located of 8 cm away from anal edge, clinical stage T3N2M0 has been diagnosed. At repeated investigation after chemoradiotherapy course on a background of significant regression of tumor, development of metastasis in rectovaginal septum was revealed, located 5 cm from the lower pole of neoplasm, that required abdominal-perineal extirpation of rectum instead of initially planned organ-preserving resection. Contrary to the standard opinion on the extremely unfavorable prognosis in patients with severe spread of tumor beyond macroscopicly visible edges, the patient was followed-up for over 3 years without signs of relapse and distant secondaries.Conclusion. Presented clinical case testifies necessity of careful preoperative investigation of patients with local spread of rectal tumors with obligatory application of magnetic-resonance tomography of small pelvis organs. In the case of prolonged radiological (chemoradiation) therapy careful investigation is required in 6–8 wks after the termination of radiation therapy, before surgical intervention. At a choice of operation risk of residual malignant process in visually unchanged tissues distally from tumor should be taken in account.